Understanding the Neural Basis of Prospective Memory Using Functional Near-Infrared Spectroscopy - Koo, Yu Wen; Neumann, David L.; Ownsworth, Tamara; Yeung, Michael K.; Shum, David H. K. (Frontiers in Human Neuroscience, 2022)
Prospective memory (PM) is the ability to perform a planned action at an intended future time. This study examined the neural correlates of PM using functional near-infrared spectroscopy (fNIRS). This study employed a within-participants design A laboratory PM task was adapted for use with fNIRS to investigate regions of interest and levels of brain activation during task performance in 32 participants (63% female, Mage=21.31 years, SDage=4.62 years). Participants first completed a working memory (WM) task (N-back ongoing task) followed by a WM plus PM task while neural activity was measured using fNIRS. Behavioural results revealed an interference effect for reaction time on the WM task, whereby participants were significantly slower to respond in the WM task plus PM Condition compared to the WM Condition. Ongoing task accuracies did not differ between the two conditions. fNIRS results revealed a higher level of neural activity in the fronto-polar prefrontal cortex and dorsolateral prefrontal cortex in the N-back plus PM task compared to the WM only task. These findings highlight that fNIRS is a suitable tool for studying and understanding the neural basis of PM.